Health and social justice - Ruger, Jennifer Prah. (Oxford : Oxford University Press, 2010)
Bringing together the latest thinking in social justice and health policy, this book seeks to integrate a capabilities perspective with the demands of health and economic policies that impact on health.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social medicine; Health -- Social aspects; Health Policy; Social justice; Equality -- Health aspects